Development of a maintenance plan for the STEPWISE project at Swerea MEFOS - Hassabelnaby, Aly (Luleå tekniska universitet, Drift, underhåll och akustik, 2018)
Process plants come with a wide variety of engineering challenges. Each process has uniqueoperating conditions that require careful operation and maintenance programs to keep the process equipment in a condition that is safe for operation. A pilot-scale plant was built in Luleå to demonstrate the possibility of carbon dioxide removal from blast furnace gas usingthe Sorption Enhanced Water Gas Shift (SEWGS) technology. One of the challenges facingthe SEWGS pilot plant was the lack of a maintenance plan which was the motivation for this thesis. The aim of this thesis was to create a maintenance plan for the SEWGS pilot plant. Studying the process conditions of the pilot plant was the starting point since an understanding of the unique operating conditions was necessary for creating a maintenance plan for the pilot plant’s equipment. The Reliability-centered maintenance (RCM) method was chosen to create the maintenance plan. The study began with determining the objectives and contents of the analysis. The next step was a functional failure analysis in the form of a Failure Mode and Effect Criticality Analysis (FMECA) covering all the equipment in the plant. Afterwards the failure consequences were assessed based on a criticality assessment matrix to determine which equipment necessitate the performance of maintenance activities. The maintenance plan was created based upon the criticality of the equipment and the selected maintenance activities were based on the recommendations of manufacturers. The failure analysis found that the blast furnace gas compressor is the most critical for the process. The boiler and superheater have been found to be highly critical due to the dangerous safety consequences of their failure. In addition, all pressure safety valves have been found to be highly critical due to the hidden nature of their failure. The maintenance plan addresses these critical items and other less critical items while some non-critical items have been removed from the plan due to the negligible consequences of ...